2002
DOI: 10.1063/1.1528288
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of sol-gel-derived Pb(Zr0.52Ti0.48)O3 thin films on a PbTiO3-coated stainless steel substrate

Abstract: Structure and properties of W O 3 -doped Pb 0.97 La 0.03 ( Zr 0.52 Ti 0.48 ) O 3 ferroelectric thin films prepared by a sol-gel process J. Appl. Phys. 98, 034104 (2005); 10.1063/1.1999834 Structure and piezoelectric properties of sol-gel-derived (001)-oriented Pb[Yb 1/2 Nb 1/2 ] O 3 -PbTiO 3 thin films J. Appl. Phys. 94, 3397 (2003); 10.1063/1.1596716 Structure and piezoelectric properties of sol-gel-derived 0.5 Pb [ Yb 1/2 Nb 1/2 ] O 3 -0.5 PbTiO 3 thin films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 10 publications
1
28
1
Order By: Relevance
“…Pt/Si and ITO coated glass substrates were ultrasonically cleaned, first in methanol then in trychloroethylene and finally in acetone. First, two layers of PT (Lead Titanate) were spin coated on both the substrates for better lattice match [6]. PMN-PT (68:32) thin films were coated using a spin coater at 3000 rpm for 20 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…Pt/Si and ITO coated glass substrates were ultrasonically cleaned, first in methanol then in trychloroethylene and finally in acetone. First, two layers of PT (Lead Titanate) were spin coated on both the substrates for better lattice match [6]. PMN-PT (68:32) thin films were coated using a spin coater at 3000 rpm for 20 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…The thermodynamic calculation indicated that two-dimensional compressive stresses could move the morphotropic phase boundary of PZT films into the titanium rich region and thus the composition of PZT (53:47) would be located at tetragonal zone [38]. It is well known that in PZT ceramics, this shift of morphotropic composition leads to sharp increasing of coercive field [27]. Thus, lower coercive voltage is expected according to the lower applied stress in high thickness sample derived by using 0.5 molar ratio of DEA.…”
Section: Effect Of Deamentioning
confidence: 98%
“…3(a) the FWHM (001) and the tetragonal lattice distortion decrease by increasing the molar ratio of DEA. The films experience the compression strain in the cooling process due to different thermal expansion coefficients of stainless steel substrate (18.4 × 10 −6 / • C) and PZT layers (9 × 10 −6 / • C) [27]. This anisotropic compression strain causes peak broadening, according to Stokes and Wilson equation [28].…”
Section: Effect Of Deamentioning
confidence: 98%
See 1 more Smart Citation
“…They are important for nonvolatile memory application because the former determines the minimal switchable voltage across film and the latter the amount of charge stored in the medium. From the experimental investigations on both lead-zirconate-titanate and strontium-bismuth-tantalate films, [1][2][3][4][5] it reveals that the coercive field decreases as the film thickness increases. In particular, similar to the ferromagnetism, 6 the relation E C ϳd n has been proposed for ferroelectric thin films; 7 where E C is the coercive field, d is the film thickness, and n is a positive integer.…”
Section: Introductionmentioning
confidence: 99%